2018
DOI: 10.3389/fpsyg.2018.01867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation on Psychophysiological Responses to Maximal Incremental Exercise Test in Recreational Endurance Runners

Abstract: Previous studies have suggested that transcranial direct current stimulation (tDCS) might improve exercise performance and alter psychophysiological responses to exercise. However, it is presently unknown whether this simple technique has similar (or greater) effects on running performance. The purpose of this study was, therefore, to test the hypothesis that, compared with sham and cathodal tDCS, anodal tDCS applied over the M1 region would attenuate perception of effort, improve affective valence, and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 62 publications
2
27
0
8
Order By: Relevance
“…The major finding in this study was that 10km cycling time trial performance was unaffected by tDCS via the Halo Sport device. Results confirm some previous findings showing that tDCS has minimal effect on exercise performance and related physiological parameters [8,[23][24][25]. In addition, it was shown that both PFC and muscle oxygenation of the vastus lateralis were maintained over the entire portion of this self-paced, 10km time trial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The major finding in this study was that 10km cycling time trial performance was unaffected by tDCS via the Halo Sport device. Results confirm some previous findings showing that tDCS has minimal effect on exercise performance and related physiological parameters [8,[23][24][25]. In addition, it was shown that both PFC and muscle oxygenation of the vastus lateralis were maintained over the entire portion of this self-paced, 10km time trial.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to those of Park et al [14] who found no change in HR responses during a constant load treadmill test after 20 minutes of Halo stimulation. Additionally, there are various studies that found no changes in HR responses during different exercises tasks following tDCS [8,23,26]. However, results of studies investigating tDCS and exercise related cardiovascular responses are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving different types of exercise intervention, including swimming, running, and cycling have found that tDCS does not influence the heart rate during exercise [ 14 , 21 , 22 ]. Additionally, a double-blind, randomized, and counterbalanced study discovered that tDCS did not influence the postexercise perceived fatigue of trained long-distance runners [ 23 ]. Park et al found that tDCS improved performance in endurance exercise without influencing heart rate, RPE, or the metabolism index [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly applying anodal tDCS to the temporal cortex (but prior to 20-km cycling time trial rather than a maximal incremental cycling task), Barwood et al [56] did not find any improvements in power output or cycling performance. Furthermore, Baldari et al [57] did not find any improvement in physiological responses (including heart rate, pulmonary ventilation, and VO2 max ), perceived exertion, affective valence, or exercise performance in recreational runners on a maximal incremental running test following anodal tDCS to the primary motor cortex. In contrast Vitor-Costa et al, [58] found an improvement in submaximal exercise tolerance in physically active subjects on a cycling task following anodal tDCS to the primary motor cortex, but this was not accompanied by changes to evaluated physiological or perceptual parameters of the sort observed in Okano's study, including the subject's heart rate and RPE.…”
Section: Enhancing Performancementioning
confidence: 93%